2012
DOI: 10.1016/j.jvs.2011.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Population-based analysis of inpatient vascular procedures and predicting future workload and implications for training

Abstract: Despite a conservative approach of using a population-based analysis of only inpatient procedures, there is a dramatic increase in the predicted vascular workload for the future. The vascular surgery training process will need to adapt to ensure an adequate number of fellowship-trained vascular surgeons is available to provide quality vascular care in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…For example, Jim et al analyzed trends in vascular procedures and predicted a 106% increase in inpatient vascular procedures alone by 2040. 6 Satiani et al did a workforce analysis and predicted a shortage of 399 surgeons by 2030. 5 Currently, the number of vascular surgery residency and fellowship positions represents a fraction of the total matches of 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Jim et al analyzed trends in vascular procedures and predicted a 106% increase in inpatient vascular procedures alone by 2040. 6 Satiani et al did a workforce analysis and predicted a shortage of 399 surgeons by 2030. 5 Currently, the number of vascular surgery residency and fellowship positions represents a fraction of the total matches of 2014.…”
Section: Discussionmentioning
confidence: 99%
“…4 Vascular surgery is on track to have significant provider shortages over the next several decades as evidenced by several prior studies. 5,6 Via population and workload analysis, Satiani et al predict a shortage of 399 vascular surgeons by 2030 5 while Jim et al predict inpatient vascular surgeon workload will increase by more than double by 2040. 6 The likely predicted shortage of vascular surgeons is dependent on several factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers [7][8][9][10] have highlighted the importance of increasing the number of VS trainees in light of conservative analyses that predict the shortage of vascular surgeons in the near future to be fairly substantial. [11][12][13] Understanding the decision-making processes of thirdand fourth-year medical students during career path selection can be vital in maintaining this interest in VS and developing new recruitment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…1 Another study of the wider population represented in the Nationwide Inpatient Sample (NIS) database showed that endovascular aortic procedures nearly tripled in the period between 1997 and 2008, while at the same time open aortic procedures dropped by nearly half. 2 Consequently, new paradigms needed to be developed to train vascular surgery fellows in endovascular procedures. By 2004, endovascular training requirements were firmly established, and were in part the impetus towards lengthening the traditional fellowship from one to two years.…”
Section: Introductionmentioning
confidence: 99%